NARRATING EDUCATION : THE ROLE OF WRITING PRACTICES IN THE PROFESSIONAL DEVELOPMENT OF EDUCATORS - Biffi, Elisabetta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The professional development of those who work in the educational sector is a theme that is widely debated at the European level. It is related to the need to guarantee high standards of educational work and high quality educational services. This paper addresses the theme from the viewpoint of the writing practices and documenting of educational work carried out by educators. Independently of the specific educational context, these professionals are called on to narrate their work, especially in written form, both as an internal record, and to externally communicate the meaning of their actions in the area where the service is based and to other stakeholders. The theory explored by the current paper is that the act of writing up their own educational work is also a valuable means of enhancing educators’ professional development.